Método de análise isotópica (δ13C) em suco clarificado de maçã - Figueira, Ricardo [UNESP]; Ducatti, Carlos [UNESP]; Mischan, Martha Maria [UNESP]; Filho, Waldemar Gastoni Venturini [UNESP] (My University, 2014)
The aims of this study were to develop the method of isotope analysis to quantify the carbon of the C3 photosynthetic cycle in commercial clarified apple juices and to measure the legal limit based on Brazilian legislation in order to identify the beverages that do not conform to the guidelines of the Ministry of Agriculture, Livestock and Food Supply (MAPA). This beverage was produced in a laboratory, according to Brazilian legislation. Adulterated juices with a sugarcane quantity above the legal limit were also produced. Isotope analyses measured the relative isotope enrichment of clarified apple juices and their purified sugar fraction. From these results the C3 source concentration was estimated by means of the isotope dilution equation. To determine the existence of adulteration in commercial juices it was necessary to create a legal limit according to Brazilian legislation. Two commercial brands of clarified juice were analyzed. Taking the C3 source concentration and the ºBrix of commercial clarified juices, together with the legal limit, it was possible to verify that one sample certainly contained more sugarcane than the quantity established by the MAPA. The development of a legal limit was an important methodological innovation that made it possible to identify the beverages that did not conform to Brazilian legislation. The methodology developed proved efficient for quantifying the carbon of C3 origin in commercial clarified apple juices.
Isotope analysis method (δ13C) in clarified apple juice
Keywords: Adulteration; Carbon-13; IRMS; Malus domestica; Sugarcane